A Chronic Lymphocytic Leukemia Patient with Progressive Multifocal Leukoencephalopathy Caused by John Cunningham Virus - Pristya Ramadhani; Bramantono Bramantono; Made Putra Sedana (Acta Medica Indonesiana)
Progressive multifocal leukoencephalopathy (PML) is a rare but fatal disease leading to severe neurological impairments. PML is a clinical manifestation, which is usually associated with John Cunningham virus (JCV) infection. It is also correlated to malignancies that mainly include hematologic malignancies such as chronic lymphocytic leukemia (CLL). Until now, no specific treatment has been established for JCV-induced PML; therefore, the prognosis of this disease is poor. We present a case of a 67-year-old woman who suffered from CLL with a chief complaint of seizure. Her clinical symptoms, results of brain MRI and biopsy were suggestive for the JCV-induced PML. The patient had received treatment using mefloquine at dose of 250 mg/day with no clinical improvement.